2019
DOI: 10.1111/jopr.13023
|View full text |Cite
|
Sign up to set email alerts
|

A Full‐Digital Technique to Mount a Maxillary Arch Scan on a Virtual Articulator

Abstract: Mounting casts accurately on an articulator is a prerequisite for the treatment planning/execution of complex dental cases that require occlusal rehabilitation. A full digital approach to transfer the position of maxillary dentition to a virtual articulator, by using intraoral scans and cone beam computed tomography (CBCT) files is presented. This technique offers reduced chairside time and the flexibility of choosing the orientation plane. It can be used in orthognathic surgeries, complex interdisciplinary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 17 publications
0
44
0
5
Order By: Relevance
“…Similar to a traditional mechanical articulator, a virtual articulator is an instrument to reproduce the position of the maxillary and mandibular dental arches, and to simulate the movement of jaw . Recently, many studies on a virtual articulator have been reported; however, most studies include mounting of the maxillary dental arch, or comparing the accuracy of articulation with a traditional mechanical articulator …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to a traditional mechanical articulator, a virtual articulator is an instrument to reproduce the position of the maxillary and mandibular dental arches, and to simulate the movement of jaw . Recently, many studies on a virtual articulator have been reported; however, most studies include mounting of the maxillary dental arch, or comparing the accuracy of articulation with a traditional mechanical articulator …”
Section: Discussionmentioning
confidence: 99%
“…This technique is a relatively simple clinical procedure to obtain the individual SCI and can assist in fabricating prosthesis to minimize the occurrence of occlusal interferences, especially in extensive reconstruction. To use this technique, mount the maxillary dental arch on a virtual articulator using the virtual facebow technique, mount the mandibular dental arch, and set the SCI on a virtual articulator …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arbitrary hinge-axis was located using Bergstrom's points (10 mm anterior to the Porion and 7 mm below the Frankfort horizontal plane) and marked with a long 3D shaft in Meshmixer (Fig 4A). 20,21 The 3D images of the face scan, intraoral scans, and skull reconstruction were superimposed within the dental CAD software to create a virtual patient. This virtual patient was mounted on a virtual articulator by matching the arbitrary hinge-axis and face ( Fig 4B).…”
Section: Clinical Reportmentioning
confidence: 99%
“…This virtual patient was mounted on a virtual articulator by matching the arbitrary hinge-axis and face ( Fig 4B). 20 With the digital articulator, the mandibular movement of the patient could be simulated according to the individualized TMJ-jaw relationship (Video 1). Average sagittal condylar inclination and Bennett angle were set on the virtual articulator.…”
Section: Clinical Reportmentioning
confidence: 99%